Thermal Melanism in Pachnoda iskuulka (Coleoptera: Scarabaeidae: Cetoniinae) - Petr Bogusch; Oto Petřík; Antonín Hlaváček; Ondřej Šebesta; Petr Šípek (Insects)
Thermal polymorphism, usually represented by thermal melanism (darker coloration in cooler habitats), is a well-known phenomenon in animals. In Cetoniinae, several species in captivity tend to become darker after several generations of breeding, which is probably caused by a lower temperature than is typical for their native habitats. Pachnoda iskuulka is a beetle species occurring in Somaliland. This species is easy to breed in captivity, and it is colorful and variable in the proportions of yellow, red, and black coloration. We kept this species from the first instar larva to the adult stage at three different temperatures. Elytra and pronotum of the adults were photographed, and proportions of the three main colors were measured. The proportion of black coloration significantly increased with size and decreased with temperature, while the proportion of yellow color increased. This species is certainly thermally polymorphic, which can be an adaptation for activation even at lower temperatures. The possible mimicry with beetles of the genus Hycleus is discussed. It is the first confirmation of thermal polymorphism in Cetoniinae and one of a few in Coleoptera.